The Effect of Critical Abilities Thinking and Logical Thinking on Student’s Physics Learning Achievement at XII SMAN 2 Palu - Bonitalia, Bonitalia; Hatibe, Amiruddin; Pasaribu, Marungkil (Jurnal Riset Pendidikan MIPA, 2019)
The purpose of this study is to analyze and examine (1) the effect of critical thinking skills on physics learning achievement, (2) the effect of the ability to think logically on physics learning achievement, (3) whether there is an influence shared between the critical thinking skills and logical thinking ability of students to the student physics achievement. This research is ex post facto. The study population was all students of class XII IPA SMA N 2 Palu that involved 292 students academic year 2016-2017. The samples in this study were students of XII Science class, 106 students were taken by purposive sampling in total which has four classes based on certain considerations. The data collection technique is using the test method for data critical thinking skills and logical thinking ability, and for students' physics learning achievement data. Data were analyzed using multiple regression analysis. The results of this study are: (i) there was a significant influence on the critical thinking skills to student physics learning achievement (R = 0.618> 0.196 at a significance level of 5%), (ii) there was a significant effect on the logical thinking ability to student physics learning achievement (R = 0.671> 0.195 at level significance 5%), (iii) there was a mutual influence between critical thinking skills and logical thinking ability to students physics learning achievement (R = 0.756, at the 5% significance level).